The effect of a tachykinin NK1 receptor antagonist, SR140333, on oedema formation induced in rat skin by venom from the Phoneutria nigriventer spider. - Palframan, R. T. (1996)
1. The possibility that tachykinin NK1 receptors are involved in the plasma extravasation evoked by intradermal (i.d.) injection of Phoneutria nigriventer venom (PNV) in rat dorsal skin in vivo has been investigated. 2. Local oedema formation induced by the i.d. injection of test agents was measured by the extravascular accumulation of intravenously (i.v.) injected 125I-labelled human serum albumin over a 30 min period. 3. The tachykinin NK1 agonist, GR73632 (30 pmol per site), induced local oedema formation which was potentiated by co-injection with the neuropeptide vasodilator, calcitonin gene-related peptide (CGRP, 10 pmol per site). The non-peptide tachykinin NK1 receptor antagonist, SR140333 (0.03-1 nmol per site co-injected, i.d.) significantly inhibited (0.3 nmol per site, P < 0.05; 1 nmol per site, P < 0.001) local oedema formation induced by GR73632 with CGRP but not that induced by histamine (10 nmol per site) with CGRP. 4. PNV (0.03-0.3 microgram per site) injected i.d. induced dose-dependent local oedema formation. SR140333 (1 nmol per site, co-injected i.d.) inhibited oedema formation; with complete inhibition observed at doses of 0.03 microgram (P < 0.05) and 0.1 microgram (P < 0.001); and partial inhibition (50%) observed with the highest dose of PNV, 0.3 microgram (P < 0.05). 5. Local oedema formation induced by PNV was not affected by systemic pretreatment with the bradykinin B2 receptor antagonist, Hoe 140 (80 nmol kg-1, i.v.), which was used at a dose which significantly inhibited oedema formation by bradykinin (1 nmol per site). 6. Local oedema formation induced by PNV was significantly inhibited (P < 0.01) by co-injection of the histamine H1 receptor antagonist, mepyramine (2.5 nmol per site), together with the 5-hydroxytryptamine (5-HT) antagonist, methysergide (2.8 nmol per site). 7. In the presence of all three antagonists (mepyramine 2.5 nmol per site; methysergide, 2.8 nmol per site and SR140333 1 nmol per site), the plasma extravasation induced by PNV was further significantly inhibited (P < 0.001, when compared with PNV injected i.d. alone; P < 0.05 when compared with PNV co-injected with mepyramine and methysergide and P < 0.01, when compared with PNV co-injected with SR140333). 8. These results suggest that oedema formation evoked by i.d. PNV in rat skin may be partially mediated via a mechanism involving tachykinin NK1 receptors and that this effect is independent of histamine and 5-HT.